2013
DOI: 10.1002/jmv.23568
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p14ARF expression by HPV‐18 E6 variants

Abstract: A common causative agent for uterine cervical cancer is the human papillomavirus type 18 (HPV-18) which has three phylogenic variants: Asian-Amerindian, European, and African. Each variant shows significant molecular differences in the E6 gene. E6 oncoprotein is a negative regulator of tumor suppressor protein p53, hence, this oncoprotein indirectly regulates the expression of tumor-suppressor p14(ARF) . p14(ARF) and p16(INK4A) genes are overexpressed in--and have been proposed as markers for--HPV-related cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…It has been reported that nucleotide changes within HPV18 E6 variant genes (Asian-Amerindian, European and African phylogenetic branches) result in different E6/E6*I splicing patterns in MCF-7 cells and cervical tumor biopsies. Interestingly, the cells and tumors harboring the Asian-Amerindian variant of E6 expressed higher levels of E6 than E6*I, while those with the African variant exhibited a higher proportion of E6*I [ 88 , 89 ]. Furthermore, European variants of HPV16 do not exhibit differences in E6/E6* splicing patterns [ 90 ].…”
Section: E6/e6* Transcription Patternsmentioning
confidence: 99%
“…It has been reported that nucleotide changes within HPV18 E6 variant genes (Asian-Amerindian, European and African phylogenetic branches) result in different E6/E6*I splicing patterns in MCF-7 cells and cervical tumor biopsies. Interestingly, the cells and tumors harboring the Asian-Amerindian variant of E6 expressed higher levels of E6 than E6*I, while those with the African variant exhibited a higher proportion of E6*I [ 88 , 89 ]. Furthermore, European variants of HPV16 do not exhibit differences in E6/E6* splicing patterns [ 90 ].…”
Section: E6/e6* Transcription Patternsmentioning
confidence: 99%
“…62,63 systems biology-based virtual cancer pathway prediction and kinetics A literature survey was performed to collect the required information about the selected protein sequences to design and predict the peptides involved in biochemical pathways. [64][65][66][67][68][69][70][71][72][73][74] A mathematical and computational model of the entire HPV45 infection signaling pathway interacting with specific genes in the presence of peptides was developed and was visualized using CellDesigner v4.4 modeling tool. 75 Nodes in the pathway represented the entities, and edges represented connectivity of one node to another, which was closely related to each other.…”
Section: Analysis Of Cross-reactivity With Human Proteomesmentioning
confidence: 99%
“…In addition, the CAVPVTTRY 4-12 epitope of E4 protein was predicted to have binding affinity for HLA-(A*29, A*30, B*58, B*35) allotypes (Table 1C). Among the five epitopes of E6 protein, RTEVYQFAF [41][42][43][44][45][46][47][48][49] and YSRIRE-LRY [72][73][74][75][76][77][78][79][80] were predicted to have binding affinity for HLA-A*(32:01, 29:02) and HLA-B*58: 01 MHC class I alleles (Table 1D). Out of 13 MHC-binding E7 peptides (Table 1E), STLSFVCPW [93][94][95][96][97][98][99][100][101] (HLA-A*32:01, HLA-B*58:01, HLA-B*57:01), LQQLFLSTL [87][88][89][90][91][92][93][94][95] (HLA-A*02:06), and QLFLSTLSF [89][90][91][92][93][94][95][96]…”
Section: Cd8 + Ctl Epitopesmentioning
confidence: 99%
See 2 more Smart Citations